2006
DOI: 10.1016/j.pain.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploding vs. imploding headache in migraine prophylaxis with Botulinum Toxin A

Abstract: Migraine headache is routinely managed using medications that abort attacks as they occur. An alternative approach to migraine management is based on prophylactic medications that reduce attack frequency. One approach has been based on local intramuscular injections of Botulinum Toxin Type A (BTX-A). Here, we explored for neurological markers that might distinguish migraine patients who benefit from BTX-A treatment (100 units divided into 21 injections sites across pericranial and neck muscles). Responders and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 40 publications
(47 reference statements)
10
134
4
Order By: Relevance
“…According to Jakubowky et al [7], pain was classified as ''explosive'' when reported as ''inside the head pointing outward'' or similar; ''implosive'' when reported as ''crushing/piercing outside the skull pointing inward'' or ''driving spikes into the head'' or similar; ''ocular'' when intraorbital pain, with the sensation of eye pulled or popped out, or pushed in, or similar. The localization of arteries was carried out by detecting their pulse with a fingertip (finger pressure on occipital arteries should be light, or the pulse frequently disappears); in a few cases, a phono-doppler apparatus was used.…”
Section: Subjects and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Jakubowky et al [7], pain was classified as ''explosive'' when reported as ''inside the head pointing outward'' or similar; ''implosive'' when reported as ''crushing/piercing outside the skull pointing inward'' or ''driving spikes into the head'' or similar; ''ocular'' when intraorbital pain, with the sensation of eye pulled or popped out, or pushed in, or similar. The localization of arteries was carried out by detecting their pulse with a fingertip (finger pressure on occipital arteries should be light, or the pulse frequently disappears); in a few cases, a phono-doppler apparatus was used.…”
Section: Subjects and Proceduresmentioning
confidence: 99%
“…Concerning the relationship between the type of pain (implosive, explosive and ocular, according to Jakubowsky et al [7]), and the response to injection, results are shown in Table 2. No significant differences were found in relief in relation to the type of pain.…”
Section: Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of these studies provide insight into which headache types might respond to BoNTA, but definitive predictors of individual patient response have not yet been identified. A single study reported a higher response rate to BoTNA when migraine patients who reported 'imploding' headaches, where pain is perceived as emanating from external pressure and includes a significant ocular component, were compared with those reporting 'exploding' headache, where pain is perceived to come from inside the head [6]. Chronic migraine is also more prevalent in women, but whether response to BoNTA differs in a sex-related manner is not known.…”
Section: Does It Work?mentioning
confidence: 99%
“…Jakubowski et al 29 found in a sample of 63 migraineurs that 74% of those who improved after BoNT-A treatment described their headache as a pressure from outside (imploding headache) or as a feeling of eyepopping (ocular headache). Conversely, 92% of those who did not respond to BoNT-A treatment described their headache as a pressure building up from inside (exploding headache).…”
Section: H E a D A C H E C H A R A C T E R I S T I C Smentioning
confidence: 99%